Epoxy Based Composite Material from the Coconut Fiber (International Journal of Scientific Research in Science and Technology, 2024)
Recently the composite material is made up of various other types of natural fibers including some epoxy resins materials. Because some natural fibers have a tendency to provide a good mechanical properties and durability also and it is safe for the environment. In this research we focused on the various testing parameters like tensile test and impact test because we won’t to have a better mechanical properties and good result also. The composite material prepared like epoxy resin with coconut fiber by using a hand laid method. The fabricated sheet is tested by various mechanical properties and it’s a very good application for us.